Research Handbook on Climate Governance 2015
DOI: 10.4337/9781783470600.00037
|View full text |Cite
|
Sign up to set email alerts
|

Civil society

Abstract: ISBN 978 1 78347 059 4 (cased) ISBN 978 1 78347 060 0 (eBook)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Although there has been an explosion of nonstate actor activity outside the UNFCCC (Fisher & Galli, ), we remain focused on the role of nonstate actors within the UNFCCC. In this institutional context, nonstate actors are increasingly on numerical parity with government delegates, and delegations also progressively include more nonstate actors (Schroeder, Boykoff, & Spiers, ; Willetts, ).…”
Section: Nonstate Actors In the Unfccc And Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there has been an explosion of nonstate actor activity outside the UNFCCC (Fisher & Galli, ), we remain focused on the role of nonstate actors within the UNFCCC. In this institutional context, nonstate actors are increasingly on numerical parity with government delegates, and delegations also progressively include more nonstate actors (Schroeder, Boykoff, & Spiers, ; Willetts, ).…”
Section: Nonstate Actors In the Unfccc And Beyondmentioning
confidence: 99%
“…The ground for exit was discontent with CAN's main pragmatic strategy that focused on inside lobbying tactics with the aim to influence negotiations: “CAN acts as lobbyists in suits instead of being watchdog environmentalists engaged in outside protests” (T. Anderson, Interview, 2013). CAN's strategy stood in sharp contrast to climate justice activists’ effort to break the fence and police line at Bella Center at COP15 in Copenhagen to take over the conference and hold the People's Assembly for Climate Justice (Fisher & Galli, ; Reitan & Gibson, , p. 402). In this instance disagreements over procedural rules (allocation of badges) and substantive normative commitments (mitigation pathways) acted as accountability standards, and members of the CJN decided to cut with CAN and exit the broader institutional framework, taking many members and resources with them.…”
Section: Institutional Accountability Through Exit Voice and Loyaltymentioning
confidence: 99%
“…In Argentina, NGOs installed a tent as an alternative meeting space in protest against extractive projects [ 81 ]. NGOs held alternative climate justice conferences nearby to United Nations climate change negotiations [ 118 ]. One study documented the development of community art projects to create space to target the tobacco industry in Indonesia [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most prevalent NGO ‘inside’ strategy targeting government and/or intergovernmental actors across the studies was lobbying policymakers, identified in 54 studies [ 13 , 23 , 26 , 29 , 32 , 36 , 40 42 , 44 , 48 , 52 , 61 , 71 , 72 , 78 , 82 85 , 89 , 93 , 97 100 , 103 , 108 , 109 , 112 , 114 116 , 118 , 120 135 ]. NGO lobbying in the literature included through formal policy processes such as submissions [ 13 , 32 , 89 , 93 , 98 , 99 , 130 , 132 , 134 , 135 ], and informal processes such as through hallway corridor conversations with policymakers [ 97 , 128 , 132 , 133 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation